Ecosystems Potency of Small and Outer Islands of Indonesia for Beef Cattle Farming Development - Inounu, Ismeth; Martindah, E.; Saptati, R A; Priyanti, A (Indonesian Animal Sciences Society, 2007)
Indonesian archipelago consists of five main islands and more than seventeen thousand of small islands. These small islands are very effective as natural barrier to the spread of contagious animal diseases. This situation is very advantageous to develop many programs such as beef cattle farming to support beef self sufficient program in 2010. However, there are some constraints in developing of these small islands, namely human resources, natural resources, infrastructure, mean of communications and transportations and lack of intra sector integrated coordination. In taking the advantageous of developing small islands as a screening base and quarantine area, animal production technologies and veterinary science are much needed. The development can be done in integration with transmigration development program so that the beef cattle development could become source of income and job opportunity for the transmigran and local inhabitant as well. Beef cattle farming scheme are recommended by doing cow-calf operation or fattening. Political support from government and legislative are needed in establishment of infrastructure in the area chosen as beef cattle farming location. Besides, it need facilitations in land procurement for beef cattle farming, legal aspect, supports of law enforcement, simple regulation in land used and zone management planning, regulation in controlling beef importation, and credit with minimum interest rate. Key words: Small islands, beef cattle, policy